(untitled) (Research, Society and Development, 2022)
The aim of this study was to describe the occurrence of feline sporotrichosis in stray animals from the Pelotas, referred to the Laboratório Regional de Diagnóstico of the Faculty of Veterinary Medicine of the Universidade Federal de Pelotas (LRD/UFPel) in the period from January 2012 to January 2022, characterizing the importance of this disease in public health, as well as to evaluate the effectiveness of the immunohistochemistry technique (IHC). The necropsy protocols of stray cats referred to the LRD/UFPel in the last 10 years were reviewed, and the epidemiological data, location of lesions, macroscopic, histopathological and mycological findings. Sections of systemic sporotrichosis cases were selected and submitted to the IHC. During this period, 28 cases of sporotrichosis were diagnosed at LRD/UFPel, 21 of which were necropsies and 7 biopsies. In 100% of the cases there was growth of Sporothrix sp. in mycological culture. In 71.4% of the cases the felines were males and 21.4% were females. Regarding the distribution of lesions, most cases corresponded to multifocal cutaneous lesions with 46.4%, followed by focal cutaneous lesions with 35.8% cases and in 17.8% cases systemic sporotrichosis was observed. It is concluded that sporotrichosis is an important cause of death in stray cats in Pelotas, with intact male cats being the most affected, limbs and head the most affected anatomical regions. The IHC technique with feline hyperimmune serum was efficient in the diagnosis.